Mechanical and durability properties of alkali-activated mortar based on sugarcane bagasse ash and blast furnace slag - Pereira, Adriana; Akasaki, Jorge L.; Melges, José L.P.; Tashima, Mauro M.; Soriano, Lourdes; Borrachero, María V.; Monzó, José; Payá, Jordi (Elsevier, 2015)
Sugarcane bagasse is an agricultural waste which can be transformed, for cementing purposes, into an interesting material by combustion. Specifically, the ash (SBA) obtained by auto-combustion was used for preparing alkali-activated cements by blending blast furnace slag (BFS). SBA had a large amount of quartz; however, it reacted in high alkaline medium. Mixtures of BFS/SBA have been used for preparing alkali-activated mortars, by using NaOH (8M solution), sodium silicate (8M solution in Na+ and SiO2/Na2O molar ratio of 0.5) and KOH (8M solution) as activating solutions. Replacements of 25%, 33% and 50% of BFS by SBA were carried out and compressive strengths in the range 16-51MPa were obtained after 90 curing days. Microstructural studies demonstrated that the hydration products formed in the activation of BFS are not significantly affected by the presence of SBA in the mixture. The durability of alkali-activated mortars was compared to ordinary Portland cement (OPC) mortar in the following media: hydrochloric acid, acetic acid, ammonium chloride, sodium sulphate and magnesium sulphate. The behaviour of alkali-activated mortars with BFS and BFS/SBA was better than that found for plain OPC mortars, especially in ammonium chloride, acetic acid and sodium sulphate media. After 200 days of testing in ammonium chloride solution, the compressive strength loss for Portland cement mortar was about 83.3%. For the same test conditions, alkali-activated mortars presented a maximum reduction of 48.4%. The presence of SBA in alkali-activated BFS mortars did not produce any serious problems in durability. As a general conclusion, sugarcane bagasse ash (SBA) obtained by auto-combustion showed good cementing properties as a mineral precursor blended with blast furnace slag (BFS) in alkali-activated systems.
Keywords: Alkali activation; Blast furnace slag; C. Strength; Durability; Sugarcane bagasse ash